1968
DOI: 10.1037/h0025807
|View full text |Cite
|
Sign up to set email alerts
|

Amygdaloid lesions and behavioral inhibition in the rat.

Abstract: Rats with bilateral lesions of the basolateral region of the amygdala were impaired in passive avoidance, DRL performance, and spatial alternations without cues, but not in visually cued spatial alternations or go-no-go visual discriminations and reversals. Except for a small deficit in passive avoidance, rats with lesions in the corticomedial region of the amygdala were not impaired in these tasks. Deficits produced by basolateral lesions can not readily be attributed to increased motivation for food or water… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
50
1
2

Year Published

1978
1978
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(67 citation statements)
references
References 49 publications
14
50
1
2
Order By: Relevance
“…Corticomedial amygdala lesioned animals do change their behaviour after the defeat but less strongly than the control animals. This observation is consistent with the partial deficits in taste aversion observed after amygdala lesions in other conditioning experiments [1,8,18,19].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Corticomedial amygdala lesioned animals do change their behaviour after the defeat but less strongly than the control animals. This observation is consistent with the partial deficits in taste aversion observed after amygdala lesions in other conditioning experiments [1,8,18,19].…”
Section: Discussionsupporting
confidence: 91%
“…For example, the effects of amygdala manipulations in avoidance situations have been interpreted in terms of reduced fear or reduced emotionality [26,28]. Also the term response suppression or performance deficit is used [5,19]. Again others [18] explain their results in taste aversion experiments in terms of a reduced capacity of amygdala lesioned animals to identify the significance or meaning of stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms of ON lesions appear to be fairly specific to taste stimuli per se (Kiefer et al,Note 2), and natrorectic adjustments to sodium depletion seem to be relatively unaffected (Wirsig & Orill, in press;Wolf et al, 1970). On the other hand, as pointed out by Nachman and Ashe, amygdaloid lesions result in a wide variety of learning deficiencies (e.g., McGowan, Hankins, & Garcia, 1972;Pellegrino, 1968) and clear disruptions of behavioral sodium homeostasis are observed (Nachman & Ashe, 1974).…”
Section: Gustatory Thalamus and Amygdalamentioning
confidence: 99%
“…Amygdaloid ablation does not interfere with rather complex tasks so long as the correct response is cued by an external environmental stimulus. For example, the acquisition of a go/no-go discrimination cued by a light and the reversal of this discrimination were not disrupted in lesioned rats (Pellegrino, 1968). On the other hand, for those tasks whose performance depends on internally formed cues for the correct response, a lesion deficit is observed.…”
mentioning
confidence: 88%
“…On the other hand, for those tasks whose performance depends on internally formed cues for the correct response, a lesion deficit is observed. For example, Pellegrino (1968) ported that lesions of the basolateral region of the nucleus impaired performance on a timing task relative to performance by a control group of rats (seealso Pubols, 1966). Likewise, Schartzbaum and Poulos (1965) reported that amygdalectomized monkeys did worse on a discrimination reversal task than did the control animals.…”
Section: David T Goomas Bayloruniversity Medical Center Dallas Texasmentioning
confidence: 99%